2017
DOI: 10.1021/acs.jnatprod.7b00506
|View full text |Cite
|
Sign up to set email alerts
|

Nicrophorusamides A and B, Antibacterial Chlorinated Cyclic Peptides from a Gut Bacterium of the Carrion Beetle Nicrophorus concolor

Abstract: Nicrophorusamides A and B (1 and 2) were discovered from a rare actinomycete, Microbacterium sp., which was isolated from the gut of the carrion beetle Nicrophorus concolor. The structures of the nicrophorusamides were established as new chlorinated cyclic hexapeptides bearing uncommon amino acid units mainly based on 1D and 2D NMR spectroscopic analysis. The absolute configurations of the amino acid residues 5-chloro-l-tryptophan, d-threo-β-hydroxyasparagine/d-asparagine, l-ornithine, l-allo-isoleucine, d-leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Subsequent chemical investigations of insect-associated actinomycetes have revealed that a Streptomyces strain found in the gut of a mealworm ( Tenebrio molitor ) produces lydiamycin A, an antitubercular cyclic peptide, and the pentaminomycin family of autophagy-inducing cyclic peptides. , Actinobacterial communities associated with carrion beetles have also produced multiple nonproteinogenic amino acid-bearing NRPs, such as antibacterial nicrophorusamides including 5-chloro-tryptophan and β-hydroxyasparagine from Microbacterium sp. found in the gut of Nicrophorus concolor and antitubercular coprisamides containing β-methylaspartic acid and 2,3-diaminopropanoic acid isolated from Micromonospora sp. found on Silpha perforata , which demonstrate their capability to produce structurally unique NRPs.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent chemical investigations of insect-associated actinomycetes have revealed that a Streptomyces strain found in the gut of a mealworm ( Tenebrio molitor ) produces lydiamycin A, an antitubercular cyclic peptide, and the pentaminomycin family of autophagy-inducing cyclic peptides. , Actinobacterial communities associated with carrion beetles have also produced multiple nonproteinogenic amino acid-bearing NRPs, such as antibacterial nicrophorusamides including 5-chloro-tryptophan and β-hydroxyasparagine from Microbacterium sp. found in the gut of Nicrophorus concolor and antitubercular coprisamides containing β-methylaspartic acid and 2,3-diaminopropanoic acid isolated from Micromonospora sp. found on Silpha perforata , which demonstrate their capability to produce structurally unique NRPs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, insects are assumed to actively associate with chemically prolific actinobacteria, which generally originate from the soil. Indeed, studying the metabolites of insect-associated actinomycetes led to the discovery of the new cyclic depsipeptide dentigerumycin [4], a geldanamycin analog natalamycin [5], the polyketide alkaloid camporidine A [6], N-acetylcysteamine-bearing indanone thioester formicin A [7], and chlorinated cyclic peptides, nicrophorusamides [8]. These bacterial secondary metabolites display antifungal, anti-inflammatory, anticancer, and antibacterial activities.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39] Therefore, we monitored all available Burkholderia endosymbionts of R. microsporus strains from highly diverse geographic regions aroundt he globe [5] for heptarhizin production( Figure 3A and B). [31][32][33][34][35][36][37][38][39] Therefore, we monitored all available Burkholderia endosymbionts of R. microsporus strains from highly diverse geographic regions aroundt he globe [5] for heptarhizin production( Figure 3A and B).…”
mentioning
confidence: 99%